Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10122798
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size, Cytotype Diversity and Reproductive Mode Variation of Cotoneaster integerrimus (Rosaceae) from the Balkans

Abstract: Cotoneaster integerrimus represents a multiploid and facultative apomictic system of widely distributed mountain populations. We used flow cytometry to determine genome size, ploidy level, and reproduction mode variation of the Balkan populations, supplemented by analysis of nuclear microsatellites in order to address: (i) geographic distribution and variation of cytotypes among the populations; (ii) variation of reproduction mode and the frequency of sexuality; (iii) pathways of endosperm formation among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Flow cytometry technology has been widely used for the detection of genome size and chromosome ploidy in horticultural plants [ 18 , 19 ]. Thus, to determine the polyploidy level of diploid and autotetraploid watermelon, we employed flow cytometry to detect the DNA content in our materials.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry technology has been widely used for the detection of genome size and chromosome ploidy in horticultural plants [ 18 , 19 ]. Thus, to determine the polyploidy level of diploid and autotetraploid watermelon, we employed flow cytometry to detect the DNA content in our materials.…”
Section: Resultsmentioning
confidence: 99%
“…The question of the biological role of one-sperm- vs. two-sperm-fertilization of central cells has been debated. The genus Sorbus belongs to the subtribe Malinae Reveal within Rosaceae that includes other genera whose reproduction modes are similar to those of Sorbus [ 39 , 46 , 47 , 48 , 49 ]. The predominance of two sperm cells over one sperm cell in the fertilization of the central cell is typical in Amelanchier Medik.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the one-sperm fertilization of the central cell is more frequent in Cotoneaster Medik. [ 48 , 49 ]. For Crataegus L. species, both alternatives were predominant in different species [ 39 , 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several geological, climatic, and biogeographical factors have been identified that have contributed to the richness and endemism of the flora of this region ( Hewitt, 1996 , 1999 ; Stevanović et al, 1999 , 2007 ; Krstić et al, 2012 ; Kougioumoutzis et al, 2021 ). Polyploidization and interspecific hybridization have played an important role especially in the evolution of many plant taxa in the Balkan Peninsula, e.g., Alyssum ( Španiel et al, 2017 ), Cardamine ( Šlenker et al, 2021 ), Centaurium ( Banjanac et al, 2017 ), Cerastium ( Niketić et al, 2013 , 2021 ), Cotoneaster ( Bogunić et al, 2021 ), Edraianthus ( Lakušić et al, 2009 ), Knautia ( Frajman et al, 2015 ), Luzula ( Bačič et al, 2016 ), Sesleria ( Kuzmanović et al, 2013 ; Lazarević et al, 2015 ), Sorbus ( Hajrudinović et al, 2015 ), Veronica ( Padilla-García et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%